Vision and voice : D.H. Lawrence, Henry Miller and Jack Kerouac as autobiographers of the soul - De Villiers, Dawid Willem, 1972- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1999.